Multiplex Gene Expression Profiling of In Vivo Isolated Circulating Tumor Cells in High-Risk Prostate Cancer Patients. (1st February 2018) - Markou, Athina; Lazaridou, Marifili; Paraskevopoulos, Panagiotis; Chen, Shukun; Świerczewska, Monika; Budna, Joanna; Kuske, Andra; Gorges, Tobias M; Joosse, Simon A; Kroneis, Thomas; Zabel, Maciej; Sedlmayr, Peter; et al.
Abstract: BACKGROUND: Molecular characterization of circulating tumor cells (CTCs) is important for selecting patients for targeted treatments. We present, for the first time, results on gene expression profiling of CTCs isolated in vivo from high-risk prostate cancer (PCa) patients compared with CTC detected by 3 protein-based assays—CellSearch ®, PSA-EPISPOT, and immunofluorescence of CellCollector ® in vivo-captured CTCs—using the same blood draw. METHODS: EpCAM-positive CTCs were isolated in vivo using the CellCollector from 108 high-risk PCa patients and 36 healthy volunteers. For 27 patients, samples were available before and after treatment. We developed highly sensitive multiplex RT-qPCR assays for 14 genes ( KRT19, EpCAM, CDH1, HMBS, PSCA, ALDH1A1, PROM1, HPRT1, TWIST1, VIM, CDH2, B2M, PLS3, and PSA ), including epithelial markers, stem cell markers, and epithelial-to-mesenchymal-transition (EMT) markers. RESULTS: We observed high heterogeneity in gene expression in the captured CTCs for each patient. At least 1 marker was detected in 74 of 105 patients (70.5%), 2 markers in 45 of 105 (40.9%), and 3 markers in 16 of 105 (15.2%). Epithelial markers were detected in 31 of 105 (29.5%) patients, EMT markers in 46 of 105 (43.8%), and stem cell markers in 15 of 105 (14.3%) patients. EMT-marker positivity was very low before therapy (2 of 27, 7.4%), but it increased after therapy (17 of 27, 63.0%), whereas epithelial markers tended to decrease after therapy (2 of 27, 7.4%) compared with before therapy (13 of 27, 48.1%). At least 2 markers were expressed in 40.9% of patients, whereas the positivity was 19.6% for CellSearch, 38.1% for EPISPOT, and 43.8% for CellCollector-based IF-staining. CONCLUSIONS: The combination of in vivo CTC isolation with downstream RNA analysis is highly promising as a high-throughput, specific, and ultrasensitive approach for multiplex liquid biopsy-based molecular diagnostics.